Ebro street mula noong isang taon - Semaña, Crista Auriel D. (Animo Repository, 2022)
The nature of relationships in today’s generation has been established within the digital world through online dating. With its growing market, the Philippines has become part of the 1.6 billion users that actively swipe for such algorithm-driven applications. In this study, it aims to shed light on the nuances of online dating and the human connections formed online and how it presents an opportunity for individuals to experience self-actualization and growth.The researchers conducted a phenomenological case study to understand the essence of the phenomenon of online dating. Using a semi-structured interview, the researchers were able to understand how online dating presents itself as a platform for finding potential partners albeit, being an avenue for different kinds of human connection that promotes self development. The results of this study will be used to supplement the film “Ebro St. Mula Noong Isang Taon” and intend to provide a sense of awareness of the human connections made online and a sense of appreciation to the interactions that encourage self expansion.